Development of keratin based hydrogels for biomedical applications - Husain, M B S; Gupta, Arun; Alashwal, B Y (IOP Publishing, 2019)
t. Synthesis of hydrogel was developed by using keratin protein extracted from a chicken feather. Further, polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), and starch have been commonly using for biomedical applications hydrogels due to their non-toxicity and, water solubility. The first sample, (KS-50) was mixed keratin, PVA/PVP and starch, the second sample, (K-50) was mixed the total weight of the (KS-50) without starch. KS-50 and K-50 were synthesized through cyclic freezing/thawing technique. Moreover, characteristics of the hydrogels, scanning electron microscopy (SEM) examined clearly exhibited porous structures, and the chemical structure of the compound was investigated by Fourier transform infrared spectroscopy (FTIR). The swelling degree of KS-50 exhibited slightly more pore size compared with K-50 hydroge